Konsep Globalisasi Dalam Buku Pelajaran PKN di MI/SD - Abdulgani Jamora Nasution; Meilyani Meilyani; Nopita Ramadhani; Lismayani Siregar (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
Globalization consists of several types, including political globalization, economic globalization, socio-cultural globalization, educational globalization, technological globalization, information and communication globalization and finally legal globalization. The existence of globalization results in all events, both in the economic, political, and socio-cultural fields that occur in one part of the world. The globalization of education is very influential in education in Indonesia, therefore, as citizens and students, they must be good at sorting out the influences of globalization that are coming. Because not all of the influences of globalization have a positive impact, of course there are also negative impacts. And at the elementary school (SD) education level, globalization is one of the subject matter that is studied and is found in Civics subjects at school. Keywords: Concept, Globalization, PKN